Kajian faktor-faktor literasi, sosialisasi dan tingkah laku pengguna terhadap perancangan kewangan Islam berdasarkan teori tingkah laku yang terancang dalam kalangan kakitangan awam di Wilayah Persekutuan, Putrajaya / Mohd Amim Othman - Mohd Amim , Othman (2017)
Islamic Financial Planning which is similar to Islamic Banking and Takaful is a new field that enters the financial market as a reaction to the activities of financial engineering by the conventional financial market movers as a result of public demand for a comprehensive service system for users of the financial markets products. Five main objectives were outlined that is first, to explore aspects related to Islamic Financial Planning covering history and financial planning evolution in the financial system in Malaysia, make comparisons based on demography for literacy, socialization factor, Islamic Financial Planning factors and financial well-being, ascertain the relationships between literacy, socialization factor and behavioral factors (attitude, subjective norms, perceived behavior control and intention) with demography, Islamic Financial Planning and financial well-being, determine the factors influencing individual‟s Islamic Financial Planning intention and behaviour and its effect on financial well-being, and objective five is to identify whether intention is a mediator in the influence by Islamic Financial Planning attitude, subjective norms and perceived behavioural control on the individual Islamic Financial Planning behaviour. The study on individual financial planning behaviour used Theory of Planned Behaviour. Multistage random sampling based on ministries and departments was used where seven ministries were selected from a list of ministries located in Putrajaya and Kuala Lumpur, Federal Territory. A total of 304 data were analysed after validity and reliabity were determined. The first objective used qualitative method based on secondary data. Firstly, the study found that global financial planning has driven the development of financial planning in Malaysia through the presence of various financial institutions in the new millennium such as the Malaysian Financial Planning Association (FPAM) and the Malaysian Financial Planning Council (MFPC). Secondly, the following involved quantitative study where Islamic Financial Planning attitude and behaviour together with financial well-being were found to be different based on marital status, job category and age. Thirdly, there was also significant relationships found between literacy, socialisation factor, Islamic Financial Planning factors and financial well-being. Fourthly, the results for objective four found that attitude (b=6.227**, p=0.000) and subjective norms (b=3.832**, p=0.000) influences Islamic Financial Planning intention. However, perceived behavioural control (b=0.457, p=0.649) was not significant in influencing the intention. For the influence on Islamic Financial Planning behaviour, the Islamic Financial Planning literacy (b=0.910**, p=0.000), perceived behavioural control (b=0.069*, p=0.017) and intention (b=0.005**, p=0.005) were found to be not influencing the behaviour. Lastly, findings of this study proved that intention acted as a mediator in the influence of attitude and subjective norms on Islamic Financial Planning behaviour. Consequently, the behaviour of Islamic Financial Planning was found to affect the financial well-being of individuals (b=0.084**, p=0.000). These show the factors in influencing Islamic Financial Planning and the effect on financial well-being of individual. The findings from this study hope to encourage the participation of individual in Islamic Financial Planning and thus may enhance their financial wellbeing.